Decision Support System for Selecting a Bus Company Using the SMART Method: A Case Study at Nuansa Utama Tour and Travel - Febriansyah, Muhammad Adam; Latipah, Latipah; Damastuti, Natalia; Junaedi, Lukman (Internet of Things and Artificial Intelligence Journal, 2024)
The rapid development of bus transportation has a significant impact on the selection of bus companies, especially travel services. Nuansa Utama Tour, a travel service agency, still uses conventional methods in selecting a Bus Company, requiring more time and process. Each Bus Company has its characteristics, so it requires a decision-weighing method that is easy to understand. This research aims to build a system that helps travel owners choose Bus Company recommendations according to the conditions and criteria needed. This system uses the Simple Multi-Attribute Rating Technique (SMART) method to determine the best Bus Company based on various criteria needed. The system development process uses the waterfall method to facilitate systematic design with the simplest possible design and the data used is taken from case study needs through the interview process so that as a result of this system, travel owners get the most Bus Company recommendations according to their needs and the best ranking, and facilitate decision making with a more flexible time before use.